Sustainable energy transition: A steam system optimization case study from a Moroccan food industry - Kawtar Ibn Batouta; Sarah Aouhassi; Khalifa Mansouri (Results in Engineering)
Industrial steam systems account for approximately 30 % of energy use in the manufacturing industry worldwide. In the context of energy transition, improving the energy efficiency of these systems is crucial, as it can significantly reduce energy losses, costs, and greenhouse gas (GHG) emissions. This study presents a comprehensive analysis of the steam system in a Moroccan agri-food plant, aiming to identify and quantify energy optimization opportunities. Initially, the Steam System Scoping Tool (SSST) benchmark revealed a score of 42.4 %, highlighting key areas for improvement. The study proceeded by diagnosing and modeling the baseline steam system, identifying major energy losses based on thermodynamic equations and Manufacturing Energy Assessment Software for Utility Reduction (MEASUR). Our study distinctively employs a systems-based approach, proposing eight energy-saving measures that holistically address all aspects of the steam system —generation, distribution, end-use, and recovery—rather than examining each component in isolation. These measures include optimizing boiler combustion, repairing insulation and leaks, reducing idle operations, and enhancing heat recovery through a feedwater economizer. Implementing these measures is projected to achieve annual energy savings of 5096 GJ, reduce CO2 emissions by 319 tons, and save $93,764, representing a 53 % reduction in the plant's thermal bill. This significant cost-saving potential should inspire optimism about the financial benefits of energy optimization, with payback periods ranging from immediate to a few months. This research marks a pioneering effort in Morocco's industrial sector, offering a replicable model that aligns with global sustainable development goals (SDGs) by reducing energy losses and enhancing production performance.